Environmental and Sustainability Issues of Indonesia Agriculture - Fahmuddin Agus (Badan Penelitian dan Pengembangan Pertanian, 2011)
Agriculture in Indonesia intensifies from the swidden to very intensive systems and expands rapidly, including tosteep slopes and peatland areas. These have implications to the environment and the system’s sustainability.Cereal and pulses-based farming systems uses moderate amount of chemicals and thus poses little threats to waterquality. However, these systems encroach into steepland accelerating erosion and depleting soil fertility. Intensivevegetable farming applies around 50 Mg/ha of barnyard manure, 300 kg/ha of N, and high rates of pesticides,posing a threat to water quality in the downstream areas. Plantation develops very rapidly, including to forest andpeatland areas. Conversion, to plantation crops, of forest (with 132300 Mg C/ha) decreases, but of shrub (with1540 Mg C/ha) and Imperata grassland (with < 5 Mg C/ha) increases the carbon stock to 3050 Mg/ha. Thetraditional tree-crop-based agriculture, characterized by a mixture of several species, reduces erosion and maintainsrelatively high carbon stock and biodiversity. Lowland rice (paddy) system, currently covering around 7.9 millionha area, has been practiced sustainably for thousands of years. Despite providing food security and variousenvironmental services, this system is under tremendous pressures of conversion to industrial and settlement areas.Meanwhile, some 20 million ha peatland of Indonesia is being converted at a rate of 1.3% annually for agricultureand silviculture. The carbon-rich land rapidly emits carbon once it is cleared and drained. Indonesian agriculturaldevelopment is challenged by the demand to keep a high level of production with minimal negative impacts to theenvironment. This can be achieved by prioritization of low carbon stock land for agricultural expansion,rationalization of fertilizer application, minimization of intensive agricultural expansion to steepland, andsafeguarding paddy field from conversion.